Consumers choice decision towards electric and conventional motorcycles - Ikhsani, Nadine Maura; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2020)
Abstract. The disadvantages of conventional motorcycles usage towards the environment as well as the very high usage of the conventional motorcycle in Indonesia, it is important to encourage people to shift from gas-powered motorcycles to electric motorcycles. This research aims to evaluate the extentto which motorcycles attributes can make people shift from conventional to electric motorcycles. Also, identify the preferable motorcycles, and calculate the elasticity of each attribute. We use choice modeling analysis to estimate the probability of a person choosing motorcycles and what attributesthat influence their decision. The research surveyed 470 respondents with criteria of people aged above 17 years old, males or females, who live in Jakarta and intend to buy motorcycles. For data processing, this research uses factor analysis, multinomial logistic regression, and demand elasticities analysis. Based on this research result, the significant attributes that influence consumers' decisions in choosing electric motorcycles are the purchase price, charging times, driving range, and also attitudes. The purchase price, safety, and Attitude are significantly influencing consumers' choice decisions on conventional motorcycles. All of the attributes are inelastic, which indicates that a change in the attributes' value will not affect the respondents' decision. Most of the respondents are more preferred to choose electric motorcycle than the conventional ones. Keywords: Consumer choice decision, electric motorcycles, conventional motorcycles